Becoming a green building professional - Henderson, Holley (Hoboken, New Jersey : John Wiley & Son, Inc., 2012)
Here is the completely up-to-date guide to today's careers in sustainable building and design -- a clear and concise survey of the field and advice for navigating a successful career. Filled with firsthand interviews with green building professionals, it covers everything from educational requirements and design specialties to the many directions in which a career in green building and design can go.
1. Why build green? -- 2. What do green building professionals do? -- 3. Green building education -- 4. Experience of green building professionals -- 5. Sustainability and green building consultants -- 6. Green building process and tools 7. Green building impact areas, people, and tools -- 8. The business of green buildings -- 9. The future of green building.
Includes bibliographical references and index.
Keywords: SUSTAINABLE ARCHITECTURE